Molecular taxonomy of Speleonectes fuchscockburni, a new pseudocryptic species of Remipedia (Crustacea) from an anchialine cave system on the Yucatán Peninsula, Quintana Roo, Mexico - Neiber, Marco T.; Hansen, Finja C.; Iliffe, Thomas M.; Gonzalez, Brett C.; Koenemann, Stefan (Zootaxa, 2012)
A new species of Remipedia (Crustacea) is described from a recently discovered section of the anchialine cave systemCenote Crustacea, situated on the northeastern coast of the Yucatán Peninsula. Speleonectes fuchscockburni n. sp. is thesecond remipede species from the Caribbean coast of Mexico. Adult specimens are relatively small and slender, with bodylengths between 12 and 16 mm, and up to 35 trunk segments. The new species can be distinguished morphologically fromS. tulumensis by sparsely setose appendages, a ventral antennular flagellum composed of 5–6 segments, and 10–12 deeplyincised denticles of the terminal maxillary and maxillpedal claws. The status of Speleonectes fuchscockburni as a new spe-cies is validated by a comparison of cytochrome c oxidase subunit I (COI) sequences from selected remipede taxa, includ-ing Speleonectes tulumensis. The uniquely high abundance of S. tulumensis in Cenote Crustacea and the distribution of the two remipedes in this cave are discussed in relation to hydrology and cave morphology.